N‐α‐acetyltransferase 10 protein is a negative regulator of 28S proteasome through interaction with PA28β. Issue 11 (26th April 2013) - Min, Li; Xu, Huiyu; Wang, Juan; Qu, Like; Jiang, Beihai; Zeng, Yan; Meng, Lin; Jin, Hongwei; Shou, Chengchao
Abstract : Naa10p physically interacts with PA28 alpha and PA28 beta by anti bait coimmunoprecipitation (View Interaction: 1, 2) Abstract : Naa10p directly interacts with proteasome activator 28β (PA28β). Naa10p interacts with PA28α in a PA28β‐dependent manner. Naa10p inhibits PA28‐dependent chymotrypsin‐like proteasome activity. Naa10p regulates 28S proteasome activity independent of acetylation.